And the band played on politics, people and the AIDS epidemic - Shilts, Randy 1951-1994 (Souvenir Press, 2011)
A masterpiece of investigative reporting, And the Band Played On is the definitive history of the spread of AIDS throughout the USA in the 1980's. Randy Shilts was employed by the 'The San Francisco Chronicle' to cover gay issues in 1981, the year AIDS came to international attention, and from 1982 Shilts devoted himself to covering the story of the disease and its medical, social and political implications. Shilts asks: how was this epidemic allowed to spread so far before it was taken seriously? Extensively researched, weaving together the personal stories of those in the gay community and the medical and political establishments with political and social reporting, he exposes how AIDS was ignored, or denied, as a threat by many national institutions. And the Band Played On shows that the greatest health crisis of the twentieth-century spread wildly as the Federal government put its budget ahead of public health while scientists were often more concerned with maintaining their prestige than saving lives.
Description based upon print version of record
Keywords: Geschichte 1980-1990; Aids; USA; Electronic books; Fiktionale Darstellung